2008
DOI: 10.1557/jmr.2008.0255
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the interfacial reaction between cation-deficient La0.56Li0.33TiO3 and metallic lithium at room temperature

Abstract: We used x-ray diffractometry (XRD), x-ray photoelectron spectrometry (XPS), and secondary-ion mass spectrometry (SIMS) to investigate the mechanism of the interfacial room-temperature (RT) chemical reaction between cation-deficient La0.56Li0.33TiO3 solid electrolytes and metallic lithium anodes in all-solid-state lithium batteries. A stoichiometric mixture of La2O3, Li2CO3, and TiO2 powders was calcined at 1250 °C for 8 h to obtain a single perovskite structure of La0.56Li0.33TiO3. When this La0.56Li0.33TiO3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…However, a new signal appears at the Ti 3+ peak for LLTO‐0.2 V. The molar ratios of Ti 4+ and Ti 3+ in LLTO‐0.2 V are ~91% and ~9%, respectively. The Ti 4+ is partly reduced by lithiation, which is consistent well with literatures . The La 3+ signals are same for all the samples, indicating that La 3+ is stable against charging (or discharging), and it is reported that La 3+ is stable even when directly in contact with Li metal …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, a new signal appears at the Ti 3+ peak for LLTO‐0.2 V. The molar ratios of Ti 4+ and Ti 3+ in LLTO‐0.2 V are ~91% and ~9%, respectively. The Ti 4+ is partly reduced by lithiation, which is consistent well with literatures . The La 3+ signals are same for all the samples, indicating that La 3+ is stable against charging (or discharging), and it is reported that La 3+ is stable even when directly in contact with Li metal …”
Section: Resultssupporting
confidence: 91%
“…Whereas, one side of the solid electrolyte is in contact with the cathode and the other side is in contact with the anode in a battery, suggesting that the solid electrolyte is working under a voltage gradient. The formation of Ti 3+ species has been observed at the interface between Li 0.33 La 0.56 TiO 3 electrolytes and lithium metal, and even titanium metal has formed for Li 0.35 La 0.55 TiO 3 after long‐term contacting with lithium metal . As a result, the phase stability, electrochemical stability, and mechanical stability are affected by the voltage gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the doping with variable‐valence elements is an effective approach to improve the electronic conductivity, which could provide donor or acceptor levels. The electronic conductions in oxides doped with variable‐valence elements are typically classified as hopping transport . All doped elements can effectively improve the electronic conductivity (Figure 4C).…”
Section: Resultssupporting
confidence: 82%
“…Ti 3+ ions largely increase the electronic conductivity and the reduction of Ti 4+ to Ti 3+ could be achieved by Li insertion or O removal. [40][41][42] The reaction of Ti 4+ /Ti 3+ by Li insertion occurs only when the voltage is below 2 V vs Li/Li + . 35 However, the voltage of the cathode coating is usually above 2 V versus Li/Li + during the operation.…”
Section: Resultsmentioning
confidence: 99%
“…By subtracting the normalized Ti 2p spectra of A-LTO from C-LTO, the two extra peaks at approximately 463.5 and 458.0 eV were attributed to Ti 3 + 2p1/2 and Ti 3 + 2p3/2 peaks; one reason for this phenomenon is the reduction of tetravalent Ti 4 + to trivalent Ti 3 + ions, resulting in the generation of high Li + concentrations. [27][28][29] The O 1s core level XPS spectra of A-LTO and C-LTO were also recorded and compared in Figure 4 b. Unlike the single O 1s peak at approximately 530.4 eV for C-LTO, the A-LTO exhibits a broader O 1s peak that can be resolved into two peaks at 529.9 and 532.0 eV.…”
mentioning
confidence: 99%